Red white and zero a film in three parts - Brook, Peter 1925-2022; Richardson, Tony 1928-1991; Delaney, Shelagh 1938-2011; More, Julian; Mostel, Zero 1915-1977; Redgrave, Vanessa 1937- (BFI, 2018)
"Woodfall Films' portmanteau feature is a major rediscovery, never before released in the UK. Comprised of three compelling tales, it brings together a trio of Britain's most innovative directors and embodies the creativity and audacity at the heart of Swinging Sixties cinema. Comic legend Zero Mostel mixes slapstick and surrealism as a tardy opera star traversing London in The Ride of the Valkyrie, while The White Bus, scripted by Shelagh Delaney, blends realism, poetry and New Wave detachment as a young woman travels home to the north of England. Tony Richardson directs Vanessa Redgrave in the final part of the film, Red and Blue, a musical, melancholic romantic reverie."
Original UK 1967
Bildformat 1.37:1
Verlagsnummer BFIB1319
Episodenfilm bestehend aus den drei Teilen The Ride of the Valkyrie, The White bus und Red and blue.
Special Features: Presented in High Definition and Standard Definition • About ‘The White Bus’ (1968, 59 mins): documentary on the making of Lindsay Anderson’s segment • Lindsay Anderson Introduction/Stills Gallery (1968, 5 mins) an audio recording of Anderson addressing the NFT in 1968, played over stills • Behind the Scenes of Red and Blue (1966, 7 mins): Kevin Brownlow’s 16mm footage of cast and crew • Kevin Brownlow on Red, White and Zero (2018, 15 mins): the Red and Blue and The White Bus editor on making the films • Billy Williams on Red and Blue (2018, 14 mins): the cinematographer recalls working with Tony Richardson on the third segment • No Arks (1969, 7 mins): political cartoonist Abu’s satirical reworking of the Noah story, narrated by Vanessa Redgrave • Audio commentary by Adrian Martin • Illustrated booklet with new writing by Sarah Wood, Paul Fairclough, So Mayer, Philip Kemp and Katy McGahan, plus full film credits
Keywords: Film; Blu-Ray-Disc; DVD-Video